The day I stopped drinking milk life stories from here and there - Murty, Sudha (New Delhi Penguin Random House, 2012)
Over the years, Sudha Murty has come across some fascinating people whose lives make for interesting stories and have astonishing lessons to reveal. Take Vishnu, who achieves every material success but never knows happiness; or Venkat, who talks so much that he has no time to listen. In other stories, a young girl goes on a train journey that changes her life forever; an impoverished village woman provides bathing water to hundreds of people in a drought-stricken area; a do-gooder ghost decides to teach a disconsolate young man Sanskrit; and in the title story, a woman in a flooded village in Odisha teaches the author a life lesson she will never forget.
Keywords: Novels -- English literature